Assessing performance of post-fire hillslope erosion control measures designed for different implementation scenarios in NE Portugal: simulations applying USLE - Figueiredo, Tomás de (2018)
Wildfires are common in NE Portugal, annually affecting large areas and contributing to increase soil degradation in a territory under severe erosion risk. Wildfires dominantly occur in forests and scrubland that cover mountain areas all over the region. Post-fire measures, required for erosion control in such hillslopes, if applied, currently lack background design. The research aimed at assessing the performance of erosion control measures in hillslopes representing different implementation scenarios in Bragança District, NE Portugal (6608 km2). Methodology applied involved building up regional scenarios for simulated application of common post-fire measures (seeding and contour barriers), using USLE procedures. Variability of precipitation, soil and slope gradient across the region was represented by 14 simulation scenarios, for which potential erosion was calculated with USLE R, K and S factors, regionally assessed in previous work by the authors. Scenarios correspond to a range of susceptibility of burnt areas across the region, represented by potential erosion. Different sediment retention degrees and spacing of contour barriers (made with burnt vegetation residues) were simulated, exploring USLE L factor to estimate their effectiveness in reducing erosion. Seeding herbaceous vegetation as a post-fire measure was simulated applying USLE C factor and considering vegetation growth rates typical of each scenario. Post-fire measures were classified according to their performance in reducing potential erosion to tolerable rates in the different implementation scenarios: low, moderate, and high performance with, respectively, erosion rates > 10 Mg ha-1 y-1, 10 – 2 Mg ha-1 y-1, and < 2 Mg ha-1 y-1. Seeding is a low performance measure and reseeding next post-fire year is recommended. Contour barriers show generally high performance, yet dependent on design parameters. In fact, increasing barrier retention degree is more effective than reducing the spacing between barriers, a result that highlights the need for well-built contour barriers. The combination of the two measures has a high performance in most scenarios, thus recommending its wide application across the region. These results point out the importance of adequately designed post-fire measures, adapted to the regional diversity of potential erosion conditions, in order to mitigate impacts and accelerate recovery of NE Portugal burnt areas.